OSEMN Approach for Real Time Data Analysis - Kajal Kumari; Mahima Bhardwaj; Swati Sharma (International Journal of Engineering and Management Research, 2020)
Data analysis system is the study of people opinions, sentiments, attitudes, and emotions expressed through written language. Sentiment analysis is just a part of it in this system we compare the accuracy result of two languages sentiment analysis. If we saw than sentiment analysis is one of the most active research areas. It is popular because of two reasons. First, it has a big range of applications because opinions are center of almost all human activities and it shows our behaviours. Whenever we make a decision, we have to heard other’s opinions as well. Second, it presents many challenges research problems, which had never been strive before the year 2000. Part of the reason for the lack of study before was that there was small dogmatic text in digital forms. There is no surprise that the establishment and the rapid growth in the field coincide with the social media on the Web. In fact, the research has also increase outside of computer science to manage science and social science due to its importance to business and society as a whole. Information analysis system is the system in which we measure the accuracy rate of both languages chirps. The main thing is this that this project is a newly formed project. We can say that sentiment analysis is just a part of it for that we have to understand what is sentiment classification and analysis. So Sentiment classification is a way to inspect the personal data in the chirps or data and then extract the opinion. Chirps analysis the method by which information is withdraw from the opinions, and emotions of people in regards to things. During decision taking the opinion of other person shave a drastic effect on users or customers ease because they make choices regarding to e-shopping, choosing events, products, things. The approaches towards chirps analysis work according to a particular level, document level. This paper aims at analysing a solution for the sentiment classification at a powdery, mainly in the sentences in which the polar nature of the chirps or sentences given by three categorization name as positive ,negative and neutral.